Feasibility of accelerometer technology with individuals with autism spectrum disorder referred for aggression, disruption, and self injury. (October 2022) - Scheithauer, Mindy; Hiremath, Shruthi; Southerland, Audrey; Rozga, Agata; Ploetz, Thomas; Rock, Chelsea; Call, Nathan
Abstract: Background: Most research on aggression, self-injury, and disruption in autism spectrum disorder (ASD) has relied on caregiver report or direct observation, both of which have limitations. Past studies demonstrate preliminary evidence for direct detection of these behaviors using accelerometers, but additional research is needed to determine the feasibility during actual clinical assessments and times when a therapist cannot be present for direct observation, as measurement during these periods has the most applied significance. Aims: This study addressed these gaps by evaluating the feasibility of accelerometer use with children with ASD and severe aggression, self-injury, and disruption in clinical and home contexts. Methods and Procedures: We evaluated the feasibility of individuals with ASD wearing accelerometers during behavioral assessments following structured habituation procedures. We also evaluated the feasibility of caregivers applying sensors to individuals with ASD in the home setting. Outcomes and Results: Most participants passed habituation and tolerated sensors during behavioral assessments (e.g., functional analyses). Caregivers applied sensors in the home with variable fidelity with wear time duration and data-collection. Conclusions and Implications: The feasibility of using accelerometers with this population is promising and should be explored further in future research. Highlights: With habituation, children with autism spectrum disorder and severe targeted behaviors can tolerate accelerometers. Tolerance achieved during habituation sessions generalizes to actual behavioral assessment sessions. Caregivers are willing to apply sensors in the home, but integrity with applying them consistently is variable.